(untitled) (Research, Society and Development, 2021)
This work aimed to identify the profile and understand the habits of consumers of meat products in the city of Fortaleza - CE. Through social networks, a questionnaire was applied seeking to understand aspects of consumption, quality and inspection of these products. It was found that 97.2% of respondents consumed meat and meat products, 70% were female and the majority (46%) with family income between 2 and 3 minimum wages. The meats with the highest consumption frequency were chicken (63.2%) and beef (32.8%); pork meat (2.5%) and fish (1.2%) had a lower prevalence of consumption. As for the place of purchase of meat products, there was a preference for supermarkets (76.7%), which can be attributed to consumers believing that this is a cleaner environment and offers a safer product for consumption. When correlating income with product choice, it was observed that, regardless of the value of family income, quality is more relevant than price, indicating that implementing food safety methods at points of sale can be considered an investment in attracting customers. Improvement measures suggested by participants included renovating the sites, training activities for traders and applying more effective enforcement strategies. Thus, it was found that consumers in the city of Fortaleza relate possible health risks to the purchase of meat products without inspection or origin. In addition, the conditions of the premises and hygiene of the establishment are also considered determining factors for the decision on choosing the place to buy meat products.